Focused ultrasound enhances targeted curcumin delivery and alleviates behavioral and neuropathological deficits in a Parkinson’s disease mouse model - Yang, Shu-Mei; Yeoh, Sen-Hi; Lin, Meng-Ting; Hsiao, Ming-Yen; Wu, Chueh-Hung; Lin, Sung-Jan; Chen, Wen-Shiang (Frontiers in Aging Neuroscience, 2026)
IntroductionCurcumin exhibits potent neuroprotective properties but is limited by poor blood-brain barrier (BBB) permeability. This study aimed to evaluate whether focused ultrasound (FUS)-mediated BBB opening enhances curcumin delivery and therapeutic efficacy in a 6-hydroxydopamine (6-OHDA) mouse model of Parkinson’s disease (PD).MethodsMale C57BL/6 mice with unilateral 6-OHDA lesions received intravenous curcumin with or without FUS targeted to the lesioned striatum for 4 weeks. Behavioral performance was assessed using rotarod and open-field tests. Postmortem analyses included tyrosine hydroxylase (TH) immunostaining in the striatum and substantia nigra pars compacta (SNpc), glial fibrillary acidic protein expression, and fluorescence quantification of curcumin accumulation. Microglial activation and pro-inflammatory cytokine expression were evaluated using ionized calcium-binding adaptor molecule 1 (Iba1) and interleukin-6 (IL-6) staining. Safety was evaluated by histological examination for hemorrhage or necrosis.ResultsSignificant improvements in motor coordination and exploratory activity were observed in the FUS + curcumin group, particularly during early stages of degeneration. Histologically, combined treatment was associated with greater preservation of TH-positive dopaminergic neurons in the SNpc and reduced astrocytic activation in the striatum compared with curcumin alone, whereas striatal TH fiber density did not differ between curcumin-treated groups. No significant differences were observed in striatal Iba1 or IL-6 expression across groups at the 4-week time point. Enhanced curcumin accumulation in the brain was observed following FUS, as demonstrated by fluorescence quantification. No tissue damage or adverse effects were observed after repeated sonications.DiscussionThis is the first study to demonstrate the efficacy of unmodified curcumin combined with FUS in a 6-OHDA PD model. The findings support FUS as a safe and effective strategy to transiently disrupt the BBB and enhance the central nervous system delivery of small-molecule therapeutic agents, offering translational potential for regionally targeted, non-invasive treatment of PD.